Identifying the source of gold geochemical anomalies in Jiaodong, eastern China: Tracking the occurrence of gold nanoparticles in a metallogenic system - Li, Ruihong; Wang, Xueqiu; Zhang, Bimin; Liu, Qingqing; Chi, Qinghua; Meng, Yinsheng; Xiong, Yuxin (Frontiers in Earth Science, 2022)
The gold particles induced geochemical anomaly shows good potential for the prospecting of gold deposits all around world. Most of the discovered gold resources are located at geochemical related anomaly area in Jiaodong, which are associated with Micro-to nanoscale particle matter. However, it has been known little about the relationship between the occurrence of gold nanoparticles and their geochemical anomaly in multimedia accommodating to the detailed process of gold mineralization system and geochemical exploration. Micro-to nanoscale gold as nanoparticles are related to the hydrothermal fluid flows and precipitation among elemental migration. This paper presents gold nanoparticles in ore, constructed the fundamental link to geochemical anomaly distribution maps of gold in drainage sediments, wall rocks, and ore, aimed to identify the source of primary and secondary geochemical anomalies according to careful observation at nanoscale gold and revealed the genesis of gold mineralization and their potential in Jiaodong. A potential model of migration pathway of gold nanoparticle was built to understand the process of massive gold accumulation and the further prospecting in the Jiaodong Peninsula.